Diagenetic Processes Overprint and Pore Types of Mauddud Formation, Badra Oil Field, Central Iraq - Faisal, Mena Jamal; Mahdi, Thamer A. (Iraqi Journal of Science, 2020)
Diagenetic processes and types of pores that control the reservoir properties are studied for Mauddud Formation in selected wells of Badra oil field, central Iraq. The microscopic study of the thin sections shows the effects of micritization, cementation, neomorphism, dissolution, dolomitization, compaction, and fracturing on Mauddud Formation carbonate microfacies. The decrease of porosity is resulted from cementation, compaction, and neomorphism. Different types of calcite cement occlude pore spaces such as drusy cement, syntaxial rim cement, and granular (blocky) cement. The neomorphism of micritic matrix and skeletal grains reduces porosity as indicated by development of microspar or pseudospar. Evidence of decreasing porosity by compaction includes closer packing of grains, which reduces interparticle porosity. Dissolution process has prominent effect in creating and increasing the effective porosity in different depositional textures of Mauddud Formation. Reservoir properties are increased in grain-supported microfacies, which have vuggy porosity or primary porosity, whose pore size differs depending on the size of the grains. The reservoir properties in the mud-supported microfacies are reduced due to the low occurrence of pores and their lack of connectivity if they exist.